Designing Non‐Newtonian Mold Powders and Optimization of Process for Continuous Casting of Billet. Issue 3 (30th August 2021) - Yang, Hyunjin; Ramirez Lopez, Pavel E.; Vasallo, Diana Mier; Cornille, Maite; Schulz, Klaus; Hunt, Adam; Stewart, Bridget
Abstract : The current article describes the approach followed to design new shear‐thinning casting powders that minimize slag entrainment without sacrificing mold lubrication during continuous casting of steel. Enhanced shear‐thinning is achieved by controlling the degree of polymerization through Si3 N4, characterized with an improved viscometry methodology where viscosity is a function of temperature as well as shear rate in contrast to the standard practice. Chemical analysis reveals a considerable loss in N accompanied by a gain in SiO2 during premelting which can represent a hindrance for industrial application. In parallel, a 3D numerical model is developed to characterize the shear‐thinning behavior through a mapping of the viscosity for temperature and shear rate. This model is used to optimize casting conditions for an industrial billet caster with electromagnetic stirring (EMS) through a response surface analysis. Finally, plant trials with the new powder show potential to reduce entrainment after postmortem analysis of the rolled materials. No critical issues are found during the industrial application despite a slight increase in mold friction and decrease in powder consumption. Ultimately, the combination of improved characterization and numerical modeling can be used as design tools for effective optimization of the shear‐thinning effects under specific casting conditions. Abstract : The article describes the approach followed to design new shear‐thinning casting powders that minimize slag entrainment without sacrificing mold lubrication during continuous casting of steel. Enhanced shear‐thinning is achieved by controlling the degree of polymerization through Si3 N4, characterized with an improved viscometry methodology where viscosity is a function of temperature and shear rate in contrast to the standard practice.